FEATURES OF VOLUME AND SQUARE LONGITUDINAL SECTION OF THYROID GLAND IN HEALTHY MEN AND WOMEN FIRST MATURE AGE - Маєвський, О.Є.; Гненна, В.О. (World of Medicine and Biology, 2014)
The article describes the age and gender features of sonographic morphometric parameters of thyroid gland in practically healthy men and women of the first mature age, urban residents of Podolia, depending on age and sex. The most pronounced differences in thyroid volume indicators established in the group 25-36 years old men compared with the 22-25 year old male. In women 25-36 years, compared to 21-25 year old female established tendency to higher values only for the volume of the left lobe of the thyroid gland. Most thyroid volume indicators set significantly higher value or tendency to higher values in men compared to women of similar age groups.
Keywords: thyroid volume; the area of the longitudinal section; sonographic study